Pengaruh Kepemimpinan, Penghargaan Terhadap Disiplin Kerja Dengan Komitmen Organisasi Sebagai Mediasi Dinas Ketenagakerjaan Kabupaten Labuhanbatu - Indah sanaya ritonga; Yudi Prayoga; Abd. Halim (STIE AMKOP, 2023)
This study aims to analyze and examine the influence of leadership and motivation on work discipline and organizational commitment. The research was conducted at the Labuhanbatu District Labor Office, the research used quantitative methods with data processing through observation, interviews, observations and questionnaires with a total of 69 respondents, with validity and reliability testing, linear regression and t testing and hypothesis testing. from research able to explain commitment as a moderating variable on the indirect influence of leadership variables and respect for work discipline at the Labuhanbatu District Labor Office. Keywords: Leadership, Motivation, Organozational Commitment, Discipline